Оптимізація розташування очисних виробок в зоні впливу на технічні свердловини - Кулібаба, С.Б.; Хохлов, Б.В.; Пакін, Ю.В. (Український науково-дослідницький і проектно-конструкторський інститут гірничої геології, геомеханіки і маркшейдерської справи НАН України, 2008)
Проанализированы результаты обследования технических скважин, подвергавшихся влиянию очистных работ в различных условиях Донбасса. Уточнена зависимость, позволяющая определить безопасную глубину подработки технических скважин. The results of inspection of technical wells that experienced the influence of stoping in different conditions of Donets Basin have been analyzed. Dependence has been corrected that allowed to define the safe depth for technical wells to be undermined.